RETRACTED: Prioritization of renewable energy sources using multi-experts Pythagorean fuzzy WASPAS (Retracted Article) - Ilbahar, Esra; Cebi, Selcuk; Kahraman, Cengiz (IOS PRESS, 2020)
Effective utilization of renewable energy sources is an essential component of countries' sustainable development strategies. A thorough evaluation of renewable energy alternatives is required to assure maximum exploitation of resources. The evaluation of renewable energy sources is a complicated problem since many criteria, even some of them are conflicting, must be taken into account simultaneously. Pythagorean fuzzy sets are better able to reflect uncertainty and vagueness in an assessment process by providing a greater domain for decision makers to describe their opinions. Therefore, this study aims at prioritizing renewable energy alternatives by employing interval-valued Pythagorean fuzzy WASPAS method. The obtained results are compared to the results of intuitionistic type-2 fuzzy WASPAS, interval-valued intuitionistic fuzzy WASPAS and crisp WASPAS methods. Biomass is selected to be the best renewable energy alternative for Central Anatolia Region of Turkey.
Keywords: Renewable energy evaluation; Pythagorean fuzzy sets; WASPAS; TECHNOLOGIES; SELECTION; CONSTRUCTION; SECTOR; AHP; Computer Science